Investigating the Coastal Livelihood in Relation to Land Use - Land Cover Change Modeling: A Case Study of Sharankhola, Bagerhat - Das, Sukanto; Ashikuzzaman, Md; Esraz Ul Zannat, Md (Journal of Bangladesh Institute of Planners, 2016)
Land-use change is a common phenomenon in coastal countries. The consequences of this phenomenon affect the coastal livelihood. Sharankhola Upazila is one of the Upazilas of coastal region of Bangladesh and has same characteristics, like other parts of the region. Land use of Sharankhola is changing day by day, like agricultural lands have been transformed into rural settlement, water body, vegetation etc. The major objectives of this study are to detect and predict the Land- use Land- cover Change (LULCC) and investigate the coastal livelihood in relation to LULCC Modeling. It is found that 22% rural settlement is increased and 20% agricultural land is decreased between 1989 and 2010 and in the year of 2025, maximum portion of the agricultural will be lost. This paper found that the rate of landless households increased alarmingly due to frequent disasters (e.g. SIDR, AILA) and it also compelled the farmers to sell their rest of the land consistently. In this study, ArcGIS, Remote Sensing software and Land Change Modeler (LCM) of IDRISI Selva is used and SPSS and Microsoft Excel are used to investigate the impact on coastal livelihood. This study can help policy makers, planners, and researchers to plan coastal region. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 1-16